A Cellular Automata based Safe Regression Test Selection Approach for Soa Based Applications - et. al., Rajanikanta Mohanty, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Service Oriented Architecture (SOA) based applications mostly comprise of heterogeneous as well as self-contained independent web services. Such applications need to be modified in order to fix the errors or with an intention to improve their underlying functionality. Incorporated such modifications are supposed to be quick and need to be supported with instant verification. Regression Test (RT) is necessary in order to guarantee the modifications should not consequently lead to any adverse effects. Regression Test Selection (RTS), considered to be one of the cheapest strategies, is intended at reducing the cost of implementation of RT. In this paper, the authors present a cellular automata based approach that enables the respective professionals for application of a safe RTS technique to SOA based applications or services in an end-to-end fashion. Safe RTS technique ensures that no modification specifying the tests should be unselected. A simplified navigational subsystem is used in this paper in order to elicit the proposed approach that incorporates 3 different services.